Collaboration model of literacy program between Forum of Reading Communities and universities in West Java Province - Rukmana, Evi Nursanti; Kusnandar, Kusnandar; CMS, Samson; Vanamamalai, Ratnamala (Faculty of Communication, Padjadjaran University, 2024)
Forum of Reading Communities West Java Province requires strengthening knowledge and inviting the younger generation to act as literacy drivers. So, the Forum of Reading Communities West Java Province collaborated with universities at West java Province. This research is to know how collaboration model of literacy program between Forum of Reading Communities West Java Province and universities. Research method used quantitative descriptive. The research results show that the Forum of Reading Communities West Java Province has collaborated with three universities, such as UNLA, UIN, and Unpad. The two of literacy program are the Ancient Bandung Literacy and Sawala Kamisan. Forum of Reading Communities West Java Province held Ancient Bandung Literacy such as a cultural stage, a Sundanese poetry reading competition, a writing village history webinar, a literacy camp, and documentation of village community culture and reading communities pioneering. Sawala Kamisan supported by teacher, lecturer, students, librarian, volunteers, and other. UNLA, UIN, and Unpad collaborated as a spekar, participant, editor, and consultant in the literacy program. Forum of Reading Communities West Java Province collaborated with universities to develop literacy program. Individual from volunteer and team from Forum of Reading Communities is the point of success this literacy program. Universities trust to Forum of Reading Communities West Java Province in implementation literacy program in the communities.